(3GdMGhj LedkG ef GdaJGhis - (3eMeO Hf eMeO Hf YHO Gddg Hf YHO GdefYe Hf YHO GdfhQ, CHh YHO Gddg GdMejQj,J (B900 (3g` s
(3ChdgG (B:s
(3CeG HYO aEfi LeYJ ai gPG GdcJGH LedkG ef aJGhi GdabgGA s
(3BNQgG (B:s
(3JUM YfOg Cfg OaY Edi GdeJhdi eKd eG MUd YfOg hGddg CYde Je GdLRA GdChd HMeO Gddg hYhfg hJhajbg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B53s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
(3GdCRgQjI s
Keywords: (3Gdabg GdTGaYjs